“Melhor em Casa!?” a resiliência do profissional frente a prática do atendimento domiciliar - Maldonado, Thais de Cassia Peixoto (2019)
Home Care started in Brazil as a practice to complement or as an alternative to existing in network processes. As population gets older, more chronic deseas starts to rise and therefore the need to humanize treatments are highlighted as main stream for long term care. In November 8th, 2011 the government program “Melhor em Casa” was launched as a commitment with Brazilian citzens with this needs. With multi-disciplinary professional and support team, the patients are assured that their clinical needs, care and frequency for treatments are effective for each and everyone of them. Also the discussion envolves the health care professional and having the resiliency as main way for diagnosys and analysis beyond the willness to contribute to necessary resources, potencial scenarios and prevention. This paper aims to understand and share the experience of professionals working with the government program highlighting the imprtance of resiliency on their routine. Using qualitative research techniques for multiple cases – mostly with semi-structured interview and photolanguage projection. To guarantee equal balance among diferent teams and functions, the participants was selection was designed to have at least one of each group. After data analysis, the goal was a deep dive in more obvious and commons pitchs to categorize the analysis. Professional Experience during Home Care: the time value; multi-disciplinary team; Two faces of the same coin; Patient humanization; Professial (re)humanization; The results indicates that the professional practice allows a closer look into the family routine to a improved and more humanized care. Home Care faces many challenges due to complex requirements, but having the network Rede de Atenção a Saúde for support allows its capabilities to makes it more reliable while accomodating the entire family because of protective and resilient aspect. Having a multi-disciplinary team with flexibility and autonomy provides a creative environment that promotes this resilient skills. However its also clear that some professionals are facing conflicts about the effectiviness and the practice of Home Care. The professionals are missing self-awareness, care and analysis to validate their emotions searching for the best experience while caring the patient, essential for the resiliency processes we are investigating